Response to population in corn hybrids with specific characteristics - Schroeder, Nathan (Kansas State University, 2013)
Examining the interaction between population and corn yield is important because the challenge of feeding the world is real. Projections show the world population is increasing and expected to reach over 9 billion people by around 2050. Expanding global urbanization drives the need to increase corn yield on current land and needs to occur to meet global population growth. Previous studies on corn yield increases conclude that ear size is limited and increasing corn plants per acre is important to increasing yield potential. This study used Answerplot data to analyze the effect of increasing plant population on corn yield in 2009. There are over 150 Answerplots across the cornbelt. The weather of 2009 proved to be a challenging year in certain regions of the cornbelt. Record rainfall, and below normal temperature had an influence on corn yield. A total of 4,180 observations from Answerplot were used from across the nation to analyze the relationship between corn yield and plant population. Multiple regression models were estimated and found that in 2009, an increase in plant population from 30,000 to 40,000 plants per acre resulted in an 8.5 bushel per acre increase. This result was robust for various econometric models. Economically, the cost per acre for current seed for this increase in population is about $38.87 per acre. At a corn price greater than $4.58 per bushel, increasing plant population would have made economic sense for 2009.
Keywords: Planting population; Yield response; Test weight response; Corn production; Moisture response